PEMBUATAN TAS BERNILAI ESTETIS DARI KULIT KERANG UNTUK MENINGKATKAN PENDAPATAN KELOMPOK PEREMPUAN NELAYAN - Surni, Surni; Azis Muthalib, Dzulfikri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Making Aesthetically Valuable Bags from Seashells to Increase the Income of Fisherwomen's Groups. This community service programme aims to empower a group of fisherwomen by making aesthetically pleasing bags from seashell waste. This initiative utilises the abundant potential of marine waste in coastal areas to create eco-friendly fashion products with high economic value. Implementation methods included training in material processing techniques, product design, and digital marketing over 6 months. The results showed a significant improvement in participants' skills, with 90% of group members able to produce bags independently. From an economic aspect, there was an average income increase of 200% (from Rp750,000 to Rp2,250,000 per month). The programme not only improved community welfare but also contributed to a 40% reduction in beach waste. These findings prove that a local resource-based empowerment approach can be a sustainable solution for coastal communities.